Anomalous metallic state underdoped infinite-layer nickelate superconducting thin films - Ting-Na Shao; Chong Sheng; Xue-yan Wang; Qiang Zhao; Fang-Hui Zhu; Wen-long Yang; Rui-Fen Dou; Chang-Min Xiong; Hai-Wen Liu; Jia-Cai Nie (Scientific Reports)
Abstract To date, the nature of the anomalous metallic state in two-dimensional systems remains unclear. In this study, we present the observation of a quantum superconductor-to-metal transition in underdoped Nd0.85Sr0.15NiO2 infinite-layer superconducting thin films, induced by a magnetic field. When a magnetic field perpendicular to the film is applied, we observed a robust intervening anomalous metallic state, characterized by a saturating resistance at low temperatures. The disappearance of Hall resistance and a huge positive magnetoresistance are the other two characteristics of boson abnormal metal state, just like the resistance tends to be saturated at low temperature. The magnetic field-regulated Nd1-xSrxNiO2 infinite-layer thin films can provide a privileged platform for investigating the details of the anomalous metallic state in a controlled manner.